Lactococcus lactis KF140 Reduces Dietary Absorption of Nε - (Carboxymethyl)lysine in Rats and Humans via β-Galactosidase Activity - Park, Ho-Young; Lee, Hye-Bin; Lee, So-Young; Oh, Mi-Jin; Ha, Sang Keun; Do, Eunju; Lee, Hyun Hee L.; Hur, Jinyoung; Lee, Kwang-Won; Nam, Mi-Hyun; Park, Myoung Gyu; Kim, Yoonsook (Frontiers in Nutrition, 2022)
Background and Aims: Excessive intake of advanced glycation end products (AGEs), which are formed in foods cooked at high temperatures for long periods of time, has negative health effects, such as inflammatory responses and oxidative stress. Nε-(Carboxymethyl)lysine (CML) is one of the major dietary AGEs. Given their generally recognized as safe status and probiotic functionalities, lactic acid bacteria may be ideal supplements for blocking intestinal absorption of food toxicants. However, the protective effects of lactic acid bacteria against dietary AGEs have not been fully elucidated. Methods: We investigated the effect of treatment with Lactococcus lactis KF140 (LL-KF140), which was isolated from kimchi, on the levels and toxicokinetics of CML. The CML reduction efficacies of the Lactococcus lactis KF140 (LL-KF140), which was isolated from kimchi, were conducted by in vitro test for reducing CML concentration of the casein-lactose reaction product (CLRP) and in vivo test for reducing serum CML level of LL-KF140 administered rats at 2.0 × 108 CFU/kg for14 d. In addition, after consuming LL-KF140 at 2.0 × 109 CFU/1.5 g for 26 days in 12 volunteers, Parmesan cheese, known to contain CML, was consumed on fasting condition, and the amount of CML contained in the blood was compared with that before intake. Results: Administration of LL-KF140 reduced serum CML levels and hepatic CML absorption in rats that were fed a CML-enriched product. In a human trial, the intake of LL-KF140 prevented increases in the serum levels of CML and alanine aminotransferase after consumption of a CML-rich cheese. Furthermore, β-galactosidase, one of the L. lactis-produced enzymes, inhibited the absorption of CML and reduced the levels of this AGE, which suggests an indirect inhibitory effect of LL-KF140. This study is the first to demonstrate that an L. lactis strain and its related enzyme contribute to the reduction of dietary absorption of CML.